Simulating Beef Cattle Herd Productivity with Varying Cow Liveweight and Fixed Feed Supply - Farrell LJ; Morris ST; Kenyon PR; Tozer PR (MDPI (Basel, Switzerland), 2021)
The liveweight of New Zealand beef cows has increased in recent decades due to selection for higher growth rates. Published data suggest that the efficiency of beef cow production decreases with increasing cow liveweight. Changes in beef herd size, feed demand, production, and cash operating surplus (COS) were simulated with average mature cow liveweight varied to 450, 500, 550, and 600 kg. With total annual beef feed demand fixed at the same level, in all scenarios cow numbers and numbers of weaned calves decreased with increasing cow liveweight. When the model was run with consistent efficiency of calf production across the mature cow liveweights (scenario A), heavier cows were more profitable. However, using published efficiency data (scenarios B and C), herds of heavier cows were less profitable. The likely most realistic scenario for New Zealand hill country farms (scenario B) had COS decrease from New Zealand Dollars (NZD) 456/ha with a herd of 450 kg cows to NZD 424/ ha with 600 kg cows. Reductions in COS were relatively small, which may not deter farmers from breeding heavier cows for higher calf growth rates. However, the results of this analysis combined with indirect potential economic impacts suggest that the heaviest cows may not be optimal for New Zealand hill country conditions.
Keywords: herd dynamics; herd size; profit; bio-economic; system dynamics; New Zealand; feed demand; efficiency; weaning weight ratio; WWR